Outage probability and capacity analysis of distributed MIMO systems over a composite fading channel - Wen-jie PENG; Yue-heng LI; Tuan-jie XUE; Mei-yan JU; Ping HUANG (Tongxin xuebao)
The exact closed-form expressions about the outage probability and capacity of distributed MIMO systems over a composite fading channel are derived firstly by using Lognormal approximation to complicated Gamma-lognormal distribution when mobile station (MS) in the cell is fixed at some position and the so-called maximum ratio transmission/selected combining (MRT-SC) and selected transmission/maximum ratio combining (ST-MRC) schemes are adopted in uplink and downlink respectively.Then based on a newly proposed non-uniform MS cell distribution model,which is more consistent with the MS cell hotspot distribution in an actual communication environment,the average outage probability and capacity formulas synthesizing the MS cell position information are further derived.Finally,the accuracy of the approximation method and the rationality of the corresponding theoretical analysis about the system performance are proven and illustrated by computer simulations.